2020
DOI: 10.1155/2020/2782396
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Papillomatosis in Adults: Assessment for Ten Years at the ENT Department of the National University Hospital of Fann (Dakar, Senegal)

Abstract: Objectives. The aim of this study was to describe the epidemiological, diagnostic, and therapeutic aspects of adult laryngeal papillomatosis in Senegal. Patients and Methods. This is a retrospective descriptive study of patients aged above 18 years with laryngeal papillomatosis and followed at the ENT department of the NUH of Fann between 01 January 2009 and 31 December 2018. Results. The mean age at diagnosis was 37.74 years and a sex ratio of 0.93. The 20–29 age group was the most represented (45.2%). The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…HPV-DNA was found in almost all laryngeal papillomatosis lesions, similar to the results observed by Sanchez 19 who reported a 95% prevalence of HPV-DNA in papillomatous lesions. The findings reported in other studies have also corroborated our results, confirming that HPV is the etiological agent of laryngeal papillomatosis 10,20,33 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HPV-DNA was found in almost all laryngeal papillomatosis lesions, similar to the results observed by Sanchez 19 who reported a 95% prevalence of HPV-DNA in papillomatous lesions. The findings reported in other studies have also corroborated our results, confirming that HPV is the etiological agent of laryngeal papillomatosis 10,20,33 .…”
Section: Discussionsupporting
confidence: 92%
“…Matos et al 23 observed the presence of HPV-6 (72%) with respect to HPV-11 (28%) in 25 patients with laryngeal papillomatosis, in a Brazilian population. Eftekhaar et al 33 observed a prevalence of 75% of HPV-6 in relation to HPV-11 (16.7%) in 12 Iranian individuals. In a Swedish study of 55 patients, Hocevar et al 35 found that 76% of patients were infected with HPV-6 and 24% with HPV-11.…”
Section: Discussionmentioning
confidence: 99%